2015
DOI: 10.1177/2041731415575870
|View full text |Cite
|
Sign up to set email alerts
|

Alginate hydrogel enriched with enamel matrix derivative to target osteogenic cell differentiation in TiO2 scaffolds

Abstract: The purpose of bone tissue engineering is to employ scaffolds, cells, and growth factors to facilitate healing of bone defects. The aim of this study was to assess the viability and osteogenic differentiation of primary human osteoblasts and adipose tissue–derived mesenchymal stem cells from various donors on titanium dioxide (TiO2) scaffolds coated with an alginate hydrogel enriched with enamel matrix derivative. Cells were harvested for quantitative reverse transcription polymerase chain reaction on days 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…All the samples coated with pillar array titanium oxide structures presented greater growth than the original samples, except for the grade V NT SI. Hence, the reason why the grade V NT SI did not increase cell growth compared to the original sample will have to be investigated, since the improvement in biocompatibility on TiO 2 surfaces compared to other surfaces has been well demonstrated [11,13,14,15,54,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…All the samples coated with pillar array titanium oxide structures presented greater growth than the original samples, except for the grade V NT SI. Hence, the reason why the grade V NT SI did not increase cell growth compared to the original sample will have to be investigated, since the improvement in biocompatibility on TiO 2 surfaces compared to other surfaces has been well demonstrated [11,13,14,15,54,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…EMD is extracted from developing porcine teeth and consists primarily of hydrophobic enamel matrix proteins including amelogenin (90%) and other nonamelogenin enamel matrix proteins (10%) . Many in vitro studies demonstrated that EMD could enhance bone regeneration through stimulating differentiation of osteogenic precursors, osteogenic differentiation of periodontal ligament cells, and activation of endothelial cells. These results indicate that EMD may be a good candidate for biofunctionalization of implant surface. Takeda et al investigated the EMD potential in improving periodontal tissue regeneration in diabetic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical application of stem cells, especially in cell therapy and tissue engineering, depends on the regulation and control of cell differentiation into specific cell types [ 13 ]. In the past decade, great efforts have been made to manipulate the differentiation of stem cells into numerous types of cells, such as osteoblast cells, neurocytes, adipocytes and cardiomyocytes [ 14 16 ]. However, the low differentiation efficiency and success rate limits the development of stem cell differentiation for stem cell therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TiO 2 can fabricate as 3D scaffolds for stem cell differentiation. TiO 2 3D scaffolds coated with alginate hydrogel containing simvastatin or enamel matrix derivative can direct osteogenic differentiation of stem cells [ 14 , 64 ]. These findings above suggest that the shape and size of TiO 2 nanoparticles has a great influence on the differentiation of stem cells, and TiO 2 nanotubes but not spherical TiO 2 nanoparticles could serve as good biomaterials for the differentiation of stem cells.…”
Section: Introductionmentioning
confidence: 99%